Atmospheric CH4 product from Svartberget (150.0 m), 2017-05-31–2026-03-31 - Eric Larmanou; Per Marklund; Mikaell Ottosson-Löfvenius; Paul Smith (Integrated Carbon Observation System, 2026)
Atmospheric CH4 concentrations, both ICOS and non-/pre-ICOS data, delivered by the Atmospheric Thematic Center
Larmanou, E., Marklund, P., Ottosson-Löfvenius, M., Smith, P. (2026). Atmospheric CH4 product from Svartberget (150.0 m), 2017-05-31–2026-03-31, European ObsPack, https://hdl.handle.net/11676/_2FYMzWroRdlmKIc92XUcbbv
Keywords: Atmosphere Thematic Centre; CH4; dry air mole fraction; time instant, UTC; time instant, UTC; quality flag; quality flag; number of points; number of points; CH4 (dry air mole fraction); CH4 (dry air mole fraction); standard deviation of gas mole fraction; standard deviation of gas mole fraction; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap